RESEARCHES OF LONG-TERM VARIATIONS IN URANUS AND NEPTUNE SPECTRA - Kuznyetsova, Yu.; Vidmachenko, A.; Matsiaka, O.; Shliakhetskaya, Y.; Yushkin, M.; Krushevska, V. (Одеські астрономічні публікації, 2016)
The results of long-term spectral observations of Solar System giant planets Uranus and Neptune are presented here. Data were obtaining in period 2002-2012 at the peak Terskol Observatory (Northern Caucasus, Russia) using 2-meter Ritchey-Chretien telescope Zeiss-2000 with help coude echelle spectrograph and at the Special astrophysical observatory (SAO RAS, Northern Caucasus, Russia) with help 6-meter telescope using echelle spectrograph NES. Raman light scattering of solar photons by hydrogen molecules in the atmosphere spectra of Uranus and Neptune was registered in most powerful Fraunhofer lines H&K CaII as the "emission" details in center cores of these lines. Relative values of Raman scattering contribution for noted lines are estimated. Also, we have carried out long-term monitoring of Raman light scattering variations in cloudy surface spectra.